Locating Leisure and Belonging in Metro Manila: From Hyper-conditioned Environments to Public Green Spaces - Saloma-Akpedonu, Czarina (Archīum Ateneo, 2021)
Leisure practices have implications for belonging. In Metro Manila, a rapidly urbanizing metropolis, leisure is becoming increasingly associated with the most ubiquitous hyper-conditioned environments: privately owned shopping malls. By decontextualizing the built environment from its natural and cultural settings, these malls present a challenge to establishing a sense of belonging within a metropolis. Yet, despite its ubiquity, the mall has not fully displaced outdoor spaces, especially public green spaces, as sites of leisure. What do leisure practices in these two seemingly contrasting environments reveal about belonging in a metropolis? Some answers to these questions are to be found in a socio-material reading of leisure spaces, which reveal how belonging is not only created by actors and social institutions but also by spaces, objects, technologies, infrastructure and the microclimate. On the basis of a qualitative study, our findings demonstrate why public green spaces are more conducive than hyper-conditioned environments for fostering a sense of belonging together and to the metropolis.